SOCIAL MEDIA AND POLITICAL PARTICIPATION: AN ANALYSIS OF YOUTH ENGAGEMENT IN ONLINE AND OFFLINE ACTIVISM - Lucy Lidiawati Santioso; Syafiq Amir; Amin Zaki; Aiman Fariq (Yayasan Adra Karima Hubbi, 2025)
A significant academic debate exists on whether youth social media engagement is slacktivism (replacement) or a gateway (mobilization) for traditional offline political participation. The field lacks empirical clarity on the specific mechanisms linking different types of online actions to offline behaviors. study aimed to: (1) empirically test the replacement versus mobilization hypotheses by disaggregating online behaviors, and (2) analyze the mediating role of political efficacy in the online-to-offline participation pathway. quantitative, cross-sectional survey was conducted with a nationally representative sample of 1,500 youth (aged 18-29). Data were analyzed using hierarchical linear regression and Structural Equation Modeling (SEM). The replacement hypothesis was refuted; no negative relationships were found. Low-cost “Expressive” participation (clicktivism) was a weak, non-significant predictor. “Organizational” online participation (e.g., creating content, coordinating groups) was the strongest, most significant predictor (β = .48, p < .001) of offline action. The SEM confirmed this link is powerfully mediated by political efficacy. slacktivism debate is resolved by this disaggregation. The study’s contribution is a refined mobilization model: high-effort “Organizational” online labor, not low-effort “Expression,” builds the political efficacy that drives offline activism.